2008
DOI: 10.1128/aem.00518-08
|View full text |Cite
|
Sign up to set email alerts
|

Joint Immobilization of Plant Growth-Promoting Bacteria and Green Microalgae in Alginate Beads as an Experimental Model for Studying Plant-Bacterium Interactions

Abstract: A simple, quantitative experimental model, offering a convenient and basic approach to studies of plantbacterium interactions, is proposed. This involves immobilizing a unicellular, freshwater microalga, a Chlorella species, serving as the plant, with a plant growth-promoting bacterium, an Azospirillum species, in small alginate beads to allow close interaction and to avoid external interference from bacterial contaminants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 57 publications
1
49
1
Order By: Relevance
“…Azospirillum spp. significantly alters the metabolism of microalgae, mainly producing indole-3-acetic acid (IAA) [78] and increasing the nitrogen cycle enzymes in these algae [73]. Although several studies described that inoculation of marine phytoplankton and freshwater bacteria sometimes increase their productivity [74], these studies are descriptive and exploratory and there is no mechanism described or demonstrated by which the phenomenon occurs.…”
Section: Probiotic Rolementioning
confidence: 99%
See 3 more Smart Citations
“…Azospirillum spp. significantly alters the metabolism of microalgae, mainly producing indole-3-acetic acid (IAA) [78] and increasing the nitrogen cycle enzymes in these algae [73]. Although several studies described that inoculation of marine phytoplankton and freshwater bacteria sometimes increase their productivity [74], these studies are descriptive and exploratory and there is no mechanism described or demonstrated by which the phenomenon occurs.…”
Section: Probiotic Rolementioning
confidence: 99%
“…De Bashan and Bashan (2008) [78], proposed and studied a model of microalgae and bacteria immobilized in alginate to analyze and evaluate their possible interactions. In their study described the following sequence of events occurring during the interaction between the two microorganisms.…”
Section: Probiotic Rolementioning
confidence: 99%
See 2 more Smart Citations
“…To achieve ideal biocontrol efficacy, the antagonists must colonize the rhizosphere soil and sustainedly occupy favorable ecological sites in the environment. Previous studies have illustrated that the long-term colonization of antagonists is correlated to soil moisture (or the water content of soil), temperature, soil aeration, pH, soil salinity, as well as the continuous supply of nutrients (Sessitsch et al, 2004;Bashan et al, 1991;Bevivino et al, 2005;Cavaglieri et al, 2005;de-Bashan and Bashan, 2008).…”
Section: Obstacles To the Long-term Colonization Of Antagonists: The mentioning
confidence: 99%